Measuring spatially resolved gas-to-dust ratios in AGB stars. Issue Volume 14:Issue S343(2019) (August 2018) - Wallström, Sofia; Dharmawardena, T.; Rodríguez Marquina, B.; Scicluna, P.; Srinivasan, S.; Kemper, F.
Abstract: Gas-to-dust ratios in Asymptotic Giant Branch (AGB) stars are used to calculate gas masses from measured dust masses and vice versa, but can vary widely and are rarely directly measured. In this work, we present spatially resolved gas and dust masses for a sample of 8 nearby AGB stars, using JCMT CO-line and continuum observations, and compare them. This serves as a pilot study for the Nearby Evolved Stars Survey (NESS; PI: P. Scicluna) project which will provide similar observations of ∼400 AGB stars in a volume-limited sample.